Pengaruh Efisiensi Teknis Terhadap Pemilihan Lokasi Penjualan pada Usaha Tambak Bandeng di Indonesia - Mahfudlotul Ula (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Milkfish farmers in Indonesia have several alternatives in selling their production,but the reality is most of them still sell their production on farm gate level. This is presumably due to the inefficient use of inputs and it has an impact on declining yields. Consequently, there’s a need for input improvement through the technical efficiency in order to increase the amount of yields, so the farmers have a stronger bargaining position and have the opportunity to access markets that offer a higher price. Therefore, the objectives of this study are (1) to measure the technical efficiency, (2) to analyze the correlation between technical efficiency and sales site choice, and (3) to analyze other factors that affect the farmers’ sale site choice. This study used data from census of agriculture 2013 as many as 1015 milkfish farmers in West Java. DEA approach is used to measure the technical efficiency, while logistic regression is used to analyze the factors that influence the farmers’ decisions. The results showed that the milkfish farmers have an average technical efficiency of 0.66. This technical efficiency had a positive influence on the selection of sale sites to the outside,  such as cooperatives, exports, and processing industries. The significant factors were age, institutional membership, education level, pond size, price, and quantity of production.